Problematika Akad Pinjaman Suka Rela Sebagai Relasi Bisnis Dalam Praktek Di Lembaga Keuangan Syariah (Studi Kasus BMT di Surabaya Utara) - Toyyibi, Abdul Majid; Bilal, Bilal; Fauzi, Muhammad (Tijarah: Jurnal Ekonomi Syariah, 2023)
Islamic financial institutions have dominated the various needs of the community, especially in BMT Nusantara and BMT Maslahah. Its existence is a great hope to be able to provide high benefits, especially non-profit financing so that the need for it will form a marker for the community of the importance of BMT in the midst of society. This research uses a type of field research with a descriptive qualitative approach, the research was carried out in the northern Surabaya area and collected data in the form of direct observation followed by direct interviews to the documentation needed in this study. In the end, data analysis was carried out previously by checking through the validity of the data using data trianggulation with the aim that the research obtained could be directed and could be accounted for its validity. The result of this study is that BMT Nusantara in its application is based on the rules and provisions of the Fiqh rules as its guidelines, while BMT Maslahah also makes the teachings of fiqh as its basis for meeting its requirements and validity. Furthermore, judging from the business strategy, it is more about the fulfillment of society in its needs so that the strategy does not interest the benefits but rather the taawun which is essentially recommended in Islamic law.